Contralateral pulmonary resection using selective bronchial blockade in postpneumonectomy patients. Issue 12 (13th October 2020) - Kawamoto, Nobutaka; Furukawa, Masashi; Okita, Riki; Okada, Masanori; Hayashi, Masataro; Inokawa, Hidetoshi; Okabe, Kazunori; Kawata, Keisuke
Abstract : Background: Pulmonary resection is occasionally performed in postpneumonectomy patients with contralateral lung lesions, such as metachronous or metastatic lung cancer. Careful intraoperative respiratory management is essential in such patients. This study evaluated the respiratory management of postpneumonectomy patients who underwent contralateral pulmonary resection with selective bronchial blockade of the lobe or segment to be resected. Methods: We retrospectively analyzed the surgical findings and safety of surgery in six patients who underwent contralateral pulmonary resection with selective bronchial blockade after pneumonectomy for non‐small cell lung cancer (NSCLC). Results: The percutaneous oxygen saturation did not decrease in any of the patients during bronchial blockade under high oxygen concentration. The median blockade time was 57.5 minutes. The operative field was tolerable secured under conditions of partial lung collapse, and partial pulmonary resection was performed as planned. Postoperatively, one patient developed acute respiratory distress syndrome due to acute exacerbation of interstitial pneumonia; however, no patients died within one month postoperatively. Two patients underwent pulmonary resection in order to obtain adequate tissue specimens to evaluate the biomarkers of multiple lung metastases. On histopathology, one patient tested positive for anaplastic lymphoma kinase (ALK) and was subsequently administered an ALK inhibitor, which prolonged survival. Conclusions: In all patients, intraoperative respiratory condition under partial lung collapse remained stable, and all partial pulmonary resections were safely performed. However, surgical indications should be carefully reviewed preoperatively in patients with interstitial pneumonia. Key points: Significant findings of the study: Contralateral partial pulmonary resection was performed using selective bronchial blockade in postpneumonectomy patients. Percutaneous oxygen saturation did not decrease during the bronchial blockade under high oxygen concentration, and the operative field was tolerable secured under conditions of partial lung collapse. What this study adds: Oxygen concentration can be set to the minimum level, sufficient to maintain oxygenation, during contralateral partial pulmonary resection with selective bronchial blockade. Abstract : In this study, contralateral pulmonary resection was performed with selective bronchial blockade in postpneumonectomy patients, and we retrospectively analyzed the surgical findings and safety of the surgery. The patients had stable intraoperative respiratory condition under partial lung collapse, and partial pulmonary resections were safe.